Effectiveness of Virtual Surgical Planning and Three-Dimensional Anatomical Models in Radiological Reconstruction of Center of Rotation and Pelvic Brim in Patients with Anterior Column Defects Requiring Revision Hip Arthroplasty - Krzysztof Andrzejewski; Marcin Domzalski; Bozena Rokita; Jan Poszepczynski; Piotr Komorowski (Diagnostics)
Background: The aim of this study was to show that virtual surgical planning (VSP) and printed anatomical models support the reconstruction of the center of rotation (COR) and pelvic BRIM during revision hip surgery using a dual-mobility revision cup system in patients with anterior pelvic column damage and soft tissue envelope deficiency. Methods: Patients with anterior pelvic column damage and soft tissue envelope deficiency underwent revision hip arthroplasty. Virtual planning included assessment of bone segmentation, positioning of the cementless revision cup while maintaining the COR, and the assumed inclination and anteversion angles. Results: The diameter of the planned revision cups was 65.5 ± 2.1 mm, and the diameter of the revision cups used was 65.3 ± 2.1 mm. The difference in COR position in the horizontal axis was 7.8 ± 9.3 mm, in the vertical axis was 4.3 ± 5.9 mm, and in the axial plane was 1.6 ± 3.3 mm. The differences in inclination angle and in the anteversion angle were 12.4° and 8.7°, respectively. Conclusions: The use of VSP and 3D models supports the process of performing RHA surgery in patients with damage to the anterior pelvic column and soft tissue envelope deficiency.